Human Corneal Endothelial Cell Assessment From Tissues Preserved in Serum-Based and Synthetic Storage Media. Issue 11 (November 2019) - Parekh, Mohit; Ruzza, Alessandro; Ponzin, Diego; Ahmad, Sajjad; Ferrari, Stefano
Abstract : Purpose: To assess the difference between endothelial cells from tissues preserved in media supplemented with fetal bovine serum (FBS) and recombinant human serum albumin (rHSA). Methods: In a donor-matched study, 48 tissues were preserved for 28 days at 31°C in Cornea Max and Cornea Syn supplemented with FBS and rHSA, respectively. Endothelial cells were visualized by 2 masked observers before and after preservation. Endothelial cell density (ECD) and the number of iatrogenic folds were counted manually. Alizarin red staining and tight junction protein (Zonula Occludens-1) were used to assess cell morphology (hexagonality and polymorphism). Intraobserver and interobserver cell counts were recorded and analyzed. Wilcoxon and one-way analysis of variance tests were used, where P < 0.05 was deemed statistically significantly different. Results: Significant amount of iatrogenic folds were observed in the tissues supplemented with FBS compared with rHSA postpreservation ( P = 0.0007). Approximately 69% and 71% hexagonal cells ( P = 0.0303) and 29% and 26% polymorphic cells ( P = 0.0234) were observed in the FBS and rHSA groups, respectively. Postpreservation, operator 1 counted 1766 cells/mm 2 in FBS and 1864 cells/mm 2 in rHSA. Operator 2 counted 1702 cells/mm 2 in FBS and 1858 cells/mm 2 in rHSA. ECD counts from FBS (interoperator) were statistically significant ( P = 0.0429). However, significance was not observed in the ECD counts (interoperator) from the rHSA-preserved tissues ( P = 0.8738). Conclusions: rHSA-supplemented media allow better visualization of the corneal endothelial cells. This reduces the rate of discard observed due to counting errors. Use of rHSA improves the current standard of care and reduces the use of animal-derived products.